Electromechanics: distance learning and remote labs - Anishchenko, Mykola; Osychev, Alexander; Shamardina, Vira; Tymoshenko, Oleksandr; Tkachenko, Andrii (National Technical University "Kharkiv Polytechnic Institute", 2016)
There is a description of three learning modules for distance learning through the Moodle environment presented; a principle of design and an order of performance of laboratory works with a distant access to real equipment is considered; tasks for individual practical works are given within each study module. The study guide is assigned for students of technical specialties under the Electromechanics direction as well as for postgraduates and engineers.
Keywords: textbook; modeling of electromechanical systems; theory of automatic control; theory of electric drive; quality of pulse АСS; frequency responses